Molecular and Environmental Mechanisms Regulating Puberty Initiation: An Integrated Approach - Livadas, Sarantis; Chrousos, George P. (Frontiers in Endocrinology, 2019)
The mechanisms underlying the initiation of puberty, one of the cornerstones of human evolution, have not been fully elucidated as yet. However, recently, an accumulating body of evidence has helped unravel several critical aspects of the process. It is clear that a change in the pattern of pituitary gonadotropin secretion serves as a hormonal trigger for puberty induction. This change is directly guided by the hypothalamic GnRH pulse generation, a phenomenon regulated by the Kisspeptin-Neurokinin-Dynorphin (KNDy) system also in the hypothalamus. This represents the kisspeptin molecule, which is crucial in augmenting GnRH secretion at puberty, whose secretion is fine-tuned by the opposing signals neurokinin B and dynorphin. Recently, the novel kisspeptin inhibitory signal MKRN3 was described, whose role in puberty initiation provided further insight into the mechanistic aspects of pubertal onset. Furthermore, the description of higher inhibitory and stimulatory signals acting upstream of the KNDy neurons suggested that the trigger point of puberty is located upstream of the KNDy system and the GnRH pulse generator. However, the mechanism of pubertal onset should not be considered as an isolated closed loop system. On the contrary, it is influenced by such factors as adipose tissue, gastrointestinal function, adrenal androgen production, energy sensing, and physical and psychosocial stress. Also, fetal and early life stressful events, as well as exposure to endocrine disruptors, may play important roles in pubertal initiation, the latter primarily through epigenetic modifications. Here we present the available data in the field and attempt to provide an integrated view of this unique and crucial phenomenon.